An Insight into Used-Products Remanufacturing - Magdalene, Andrew-Munot (Penerbit Akademia Baru, 2015)
Nowadays, remanufacture of used-products is gaining importance amongst many manufacturers as well as third party companies. This paper identifies the main drivers for remanufacturing to be product take-back legislations, environmental concerns and economic benefits. This paper also identifies the four main remanufacturing processes to be inspection & grading, disassembly & inspection, component reprocessing and reassembly. Finally, this paper presents several examples of remanufactured products and the two markets for selling them. This paper provides valuable insights on remanufacturing to potential remanufacturers, researchers and the general public. Remanufacturing in the long run can save materials, cost and the environment.